2022
DOI: 10.1111/nbu.12547
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and food poverty conversations: Social network analysis of Twitter data

Abstract: This novel and mixed‐method study investigated food poverty conversations at the beginning of the COVID‐19 pandemic and the subsequent national lockdown on the social media platform Twitter. NodeXL Pro software was used to collect tweets using the terms ‘food’ and ‘poverty’ in any order somewhere in a tweet sent on selected days between April 5 and May 23, 2020. The data obtained from NodeXL Pro were cleaned. Social network analysis tools were used to analyse and visualise our data. Using this method, sentimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“… 32 Overall, SNA allows for examining social media conversations to understand public discourse around important social issues. 33 …”
Section: Discussionmentioning
confidence: 99%
“… 32 Overall, SNA allows for examining social media conversations to understand public discourse around important social issues. 33 …”
Section: Discussionmentioning
confidence: 99%
“…This is the first work that examines X activity associated with the use of #NutritionFacts. Previous diet-related X analysis have examined the nutrition-information relevance of 298 tweets containing the hashtag #heartfailure ( 32 ) 2,886 tweets of dietitians and users sharing nutrition information during COVID-19 ( 36 ) and 81,249 tweets that contained combination of the terms ‘food’ and ‘poverty’ during the COVID-19 pandemic ( 37 ). Interestingly, the healthcare stakeholders analysis performed by us ( Figure 1 ) indicated that the top ten list contained diverse organizational categories with the most prominent stakeholder being organizations fulfilling roles within the healthcare industry but not providing direct clinical care ( Org.…”
Section: Discussionmentioning
confidence: 99%
“…To maximise tweet collection, daily queries were conducted throughout the study, but due to API limitations, Twitter data could not be collected beyond December 17. The collected (Ahmed et al, 2020;Eskandari et al, 2022;Pascual-Ferrá et al, 2022;Rauchfleisch et al, 2021;Wiiava & Handoko, 2021;Yum, 2020;Zeemering, 2021). In the present article, SNA was used to visualise the network structure and detect network communities.…”
Section: Social Network Analysis and Quantitative Content Analysismentioning
confidence: 99%